Statement on the active substance flupyradifurone. (24th January 2022) - ,; Hernandez Jerez, Antonio; Adriaanse, Paulien; Berny, Philippe; Coja, Tamara; Duquesne, Sabine; Focks, Andreas; Marinovich, Marina; Millet, Maurice; Pelkonen, Olavi; Pieper, Silvia; Tiktak, Aaldrik; et al.
Abstract: Flupyradifurone is a novel butenolide insecticide, first approved as an active substance for use in plant protection products by Commission Implementing Regulation (EU) 2015/2084. Following concerns that this substance may pose high risks to humans and the environment, the French authorities, in November 2020, asked the Commission to restrict its uses under Article 69 of Regulation (EC) No 1107/2009. To support this request, competent Authorities from France cited a series of literature papers investigating its hazards and/or exposure to humans and the environment. In addition, in June 2020, the Dutch Authorities notified the Commission, under Article 56 of Regulation (EC) No 1107/2009, of new information on flupyradifurone on the wild bee species Megachile rotundata . This notification is also referred to in the French notification on flupyradifurone. Consequently, the EFSA PPR Panel was mandated to quantify the likelihood of this body of evidence constituting proof of serious risks to humans or the environment. Therefore, the EFSA PPR Panel evaluated the likelihood of these studies indicating new or higher hazards and exposure to humans and the environment compared to previous EU assessments. A stepwise methodology was designed, including: (i) the initial screening; (ii) data extraction and critical appraisal based on the principles of OHAT/NTP; (iii) weight of evidence, including consideration of the previous EU assessments; (iv) uncertainty analysis, followed, whenever relevant, by an expert knowledge elicitation process. For the human health, only one study was considered relevant for the genotoxic potential of flupyradifurone in vitro . These data did not provide sufficient information to overrule the EU assessment, as in vivo studies already addressed the genotoxic potential of flupyradifurone. Environment: All available data investigated hazards in bee species. For honey bees, the likelihood of the new data indicating higher hazards than the previous EU assessment was considered low or moderate, with some uncertainties. However, among solitary bee species – which were not addressed in the previous EU assessment – there was evidence that Megachile rotundata may be disproportionately sensitive to flupyradifurone. This sensitivity, which may partially be explained by the low bodyweight of this species, was mechanistically linked to inadequate bodily metabolisation processes. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2022.7031/full